PRELIMINARY OBSERVATIONS ON THE MORPHOMETRIC CHARACTERISTICS, LENGTH WEIGHT RELATIONSHIP, FOOD AND FEEDING HABITS AND FECUNDITY OF SAURIDA TUMBIL (BLOCH) OFF BOMBAY COAST - SINGH, V. N.; ACHARYA, P.; JAISWAR, A. K. (Journal of Indian Fisheries Association, 2015)
Fifteen morphometric and four meristic characters of Saurida tumbilwere studied and their relationships with total length and head lengthwere established. The length weight relationship worked out to be W=-5.6055 L 3·291. The fish is a carnivore, feeding mainly on small fishes,molluscs and crustaceans. Larger fishes are selective feeders on fish. Itis a long protracted spawner. Fecundity varied from 6008 to 17384 eggsin specimens of size group 212-420 mm. Fecundity-total length, fecunditytotalweight of fish and fecundity • total weight of ovary relationshipswere worked out to be F=0.9414 LL6626• F=180.7069 wo.7531 and F=3153.0375W0·8278 respectively